The Effect of Information on Market Activity; Evidence from Vehicle Recalls - Inge van den Bijgaart; Davide Cerruti (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We evaluate the effect of vehicle recalls on vehicle transactions in the second-hand market. Using a rich dataset of Dutch vehicle registrations, we exploit the quasi-experimental variation in recalls across nearly-identical cars. We find strong heterogeneities across market segment: vehicles with a lower (higher) list price or some (zero) defects experience an increase (decrease) in transactions after a recall. Based on our theoretical model, this suggests that recalls increase sorting in low-end markets, yet exacerbate adverse selection in high-end markets. Our results shed light on the effect of information arrival in markets subject to uncertainty and information asymmetries.
Keywords: D12; D83; L15; L62; 330; vehicles; recalls; adverse selection; sorting; information